Perundungan Siber (Cyberbullying) Melalui Media Sosial Instagram dalam Teori the Space Transition of Cybercrimes - Aroma Elmina Martha (Fakultas Hukum Universitas Islam Indonesia, 2024)
Spatial transition theory defines that people behave differently in the cyber world than in the physical world. This theory attempts to explain patterns of cyber-criminal behavior by categorizing cyber-crimes into four main categories of cyber offenses, namely violent behavior, cyberbullying, fraud, cyber theft, and cyber pornography. The topic of cyber bullying is highlighted in this study since this behavior appears to have turned into something that is taken lightly in Indonesian society. Acts of bullying in cyberspace are carried out without burden by the perpetrator. The belief that bullying behavior becomes tolerated and will not raise legal consequences had made the perpetrator feel free. Bullying brings effects to the victim which severely impact their psychological welfare, which may even lead to depression and even death. This research describes cyberbullying behavior in the study of the spatial transition of cybercrimes theory as an effort to examine and to identify the background of why the perpetrator has the heart and courage to commit such crime. By utilising a criminological approach, the data collected were classified with cases of cyberbullying in the previous year of 2022-2023, in the form of social media information via Instagram. This research explores cases of cyberbullying which mainly poses an impact on the psychological losses of victims of crimes that occur on social media in Indonesia. This research is expected to provide an understanding of cybercrime patterns for the purpose of preventing cyberbullying behavior.Keywords: Bullying; Criminology; Cyberspace. AbstrakTeori transisi ruang menjelaskan bahwa orang memiliki perilaku yang berbeda di dunia siber dengan dunia fisik. Teori ini berupaya menjelaskan pola perilaku kriminal siber dengan mengkategorikan kejahatan dunia maya ke dalam empat jenis utama pelanggaran dunia maya yaitu perilaku kekerasan cyberbullying, penipuan, pencurian di dunia maya, dan pornografi dunia maya. Topik cyberbullying ini dipilih karena perilaku ini seolah telah menjadi norma yang dilonggarkan dalam masyarakat Indonesia. Tindakan bullying di dunia maya dilakukan tanpa beban oleh pelaku. Adanya keyakinan bahwa perilaku perundungan merasa aman dan tidak akan menimbulkan akibat hukum membuat pelaku merasa bebas. Efek yang ditimbulkan terhadap korban memberi pengaruh psikologi yang berat, bahkan sampai pada depresi bahkan kematian. Penelitian ini menguraikan perilaku cyberbullying dalam kajian teori the space transition of cybercrimes sebagai upaya mengidentifikasi dan mengetahui latar belakang mengapa pelaku tega dan berani melakukan kejahatan ini. Dengan menggunakan pendekatan kriminologis, data yang diambil dikelompokkan dengan kasus-kasus cyberbullying dalam satu tahun terakhir, 2022-2023, dalam bentuk informasi media sosial melalui Instagram. Riset ini menggali kasus cyberbullying yang utamanya berdampak pada kerugian psikis dari korban kejahatan yang terjadi di media sosial di Indonesia. Riset ini diharapkan memberikan pemahaman mengenai pola kejahatan cybercrimes sehingga dapat mencegah terjadinya perilaku cyberbullying.Kata Kunci: Dunia Maya; Kriminologi; Perundungan.